Cardiac MRI as a diagnostic tool in pulmonary hypertension. (January 2014) - Alassas, Khadija; Mergo, Patricia; Ibrahim, El-Sayed; Burger, Charles; Safford, Robert; Parikh, Pragnesh; Shapiro, Brian
ABSTRACT: Pulmonary hypertension is characterized by alterations in the viscoelastic properties of the pulmonary arteries, leading to increased pulmonary arterial stiffness and elevated pressures. Early detection and accurate quantification of pulmonary hypertension are limitations to conventional noninvasive imaging and may have therapeutic implications. Cardiac MRI provides important information that can aid the clinician, particularly relating to morphologic right ventricular alterations and quantification of stiffness, as well as providing a novel prognostic framework.